(untitled) (Jurnal Bahasa, 2006)
This research focuses on the phonological errors of native speakers of Iban language in the process of mastering standard Malay. It aims at identifying the standard Malay phonemes that cannot be mastered by native speakers of Iban language, based on data collected from 20 pupils of two primary schools in the Tutong district in Negara Brunei Darussalam. The data is based on a corpus of 84 selected words which represent the 31 standard Malay phonemes. The finding shows that there are 15 phonemes of standard Malay that cannot be pronounced properly by the Iban speaking pupils in the school, i.e 12 consonants and 3 vowels. Pronunciation difficulty occurs as the result of the absence of these phonemes in the Iban language phonological system. The finding shows direct transfer of the Iban phonological system into the standard Malay phonological system.